Authorship and Attribution in the Wurstisen Lute Book - Yavor Genov (De Musica Disserenda, 2024)
The so called Wurstisen Lute Book (CH-Bu, Ms. F.IX.70) is a remarkable anthology containing a huge repertory that was written down in German lute tablature at the end of the sixteenth century. Serving most likely as a private music collection, it relatively infrequently contains names or indications of authors. The present article deals with what the scribe has left in the way of indications, shedding more light on, and interpreting, some of them. Additionally, the research suggests some sources that may have been at the disposal of the compiler, Emanuel Wurstisen, or were possibly related to his book when they came to be printed years later.